2017
DOI: 10.1007/s00198-017-4153-6
|View full text |Cite
|
Sign up to set email alerts
|

Costs of fragility hip fractures globally: a systematic review and meta-regression analysis

Abstract: Purpose This study was conducted in order to systematically review the costs of hip fractures globally and identify drivers of differences in costs. Methods A systematic review was conducted to identify studies reporting patient level fragility hip fracture costs between 1990 and 2015. We extracted data on the participants and costs from these studies. Cost data concerning the index hospitalisation were pooled, and a meta-regression was used to examine its potential drivers. We also pooled data on the first-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
121
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(132 citation statements)
references
References 26 publications
5
121
0
6
Order By: Relevance
“…Each year in the United Kingdom, 1.8 million fractures occur with an annual incidence of about 3.6% and a lifetime prevalence of approximately 40% (1,2,3). The annual cost in the United Kingdom for hip fractures alone including medical and social care is about £2 billion (4).…”
Section: Introductionmentioning
confidence: 99%
“…Each year in the United Kingdom, 1.8 million fractures occur with an annual incidence of about 3.6% and a lifetime prevalence of approximately 40% (1,2,3). The annual cost in the United Kingdom for hip fractures alone including medical and social care is about £2 billion (4).…”
Section: Introductionmentioning
confidence: 99%
“…e annual expenditure associated with osteoporotic fractures and osteoporosis is estimated to be greater than that identified in this study (USD 34 million), as the expenditure identified in this study only quantifies the expenditure associated with the management of the osteoporotic hip fracture and not the expenditure on the annual monitoring of fracture, in other fracture types, in tests used for the diagnosis of osteoporosis, or in the treatment of osteoporosis. e costs of medical treatment during the year following the surgery in the US vary in a range from $21,559 to $44,200, which is influenced by the local health policy that influences the effectiveness of the handling of this pathology [10]. Within the limitations of the work, it can be mentioned that the complications of prolonged rest or surgical procedures and infection of the operative pathway, venous thrombosis, or pulmonary thromboembolism among others were not considered in the evaluation of the direct economic impact of hip fractures.…”
Section: Discussionmentioning
confidence: 99%
“…e cost of the initial hospitalization in the treatment of osteoporotic hip fractures in the public system of Chile is similar to that of Latin American countries such as Uruguay and Argentina (3-4 thousand dollars) [19], while the cost in the private health system is similar to that of European countries such as Belgium (9 thousand dollars) [27], being very close to the world average (10 thousand dollars) [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hip fracture is by far the most common reason for hospital admission, it may occurs either as a result of a fragility fracture (Acevedo et al, 2018) or a fall. Most hip fracture patients receive operative treatment (Weycker et al, 2016;Williamson et al, 2017). The ability of the proximal femur to bear the internal load actions resulting from a fall is significantly reduced by osteoporosis and in particular, it has been demonstrated that this is related to reduced areal bone mineral density (Curtis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%